PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP TAX AVOIDANCE (Studi Empiris pada Perusahaan Pertambangan yang Terdaftar di BEI Tahun 2021 - 2023) - Laila Maghfiroh; Herry Laksito (Diponegoro Journal of Accounting, 2025)
This This study aims to examine the effect of leverage and profitability on tax avoidance in mining companies listed on the Indonesia Stock Exchange (IDX) during the period 2021–2023. Tax avoidance is measured using the Current Effective Tax Rate (CETR). Profitability is proxied by Return on Assets (ROA), while leverage is proxied by the Debt to Equity Ratio (DER). The population in this study includes all mining sector companies listed on the IDX, with a total sample of 108 companies selected through purposive sampling based on specific criteria. The data analysis technique employed is multiple linear regression using SPSS version 26. The results show that profitability has no significant effect on tax avoidance. Meanwhile, leverage has a positive and significant effect on tax avoidance.